E-Vokids (English Vocabulary for Kids): Aplikasi Berbasis Augmented Reality untuk Media Pembelajaran Bahasa Inggris - Virninda, Andi Nurul; Djatmiko; Adelynn Calysta; Risman (Jurnal Pembelajaran Inovatif, 2025)
This research aims to develop an English vocabulary learning application using augmented reality to find the application's feasibility test outcomes. The research methodology used is Research and Development (R&D) with a prototype development model consisting of several stages: Analysis, Design, Coding, and Testing. The results of this research are an augmented reality-based application, E-Vokids (English Vocabulary for Kids), as an English learning application used on Android-based smartphones. With a test percentage of 100% and marker testing, it is concluded that the markers used are very decent; the results of the application testing, which consists of functionality testing, are also very decent. The feasibility test is based on user responses from 30 students of SMPS Makassar Raya Obtained a "very decent" With an average feasibility percentage of 85.35, the application is categorized as very decent. Based on the results of this research, the E-Vokids are viable to be used as an English vocabulary learning application.